2019
DOI: 10.1007/s11695-019-03909-1
|View full text |Cite
|
Sign up to set email alerts
|

Bone Turnover Markers After Standard and Distal Roux-en-Y Gastric Bypass: Results from a Randomized Controlled Trial

Abstract: Background Roux-en-Y gastric bypass is associated with increased risk of bone fractures. Malabsorptive procedures may be associated with secondary hyperparathyroidism and detrimental effects on bone health. We aimed to compare the effects of standard and distal gastric bypass on bone turnover markers 2 years after surgery. Methods Patients with body mass index (BMI) 50-60 kg/m 2 (n = 113) were randomized to standard or distal gastric bypass, 105 patients (95%) completed 2-year follow-up. Serum C-terminal telop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 32 publications
0
18
0
1
Order By: Relevance
“…Levels of the bone turnover marker CTX-1 and parathyroid hormone increased more after distal than standard RYGB. The prevalence of secondary hyperparathyroidism was also higher after distal compared with standard RYGB, corresponding to findings after 2 years 34 . Higher levels of bone turnover markers are associated with faster bone loss and predict fractures, even after adjustment for aBMD 35–37 .…”
Section: Discussionmentioning
confidence: 53%
“…Levels of the bone turnover marker CTX-1 and parathyroid hormone increased more after distal than standard RYGB. The prevalence of secondary hyperparathyroidism was also higher after distal compared with standard RYGB, corresponding to findings after 2 years 34 . Higher levels of bone turnover markers are associated with faster bone loss and predict fractures, even after adjustment for aBMD 35–37 .…”
Section: Discussionmentioning
confidence: 53%
“…Individuals with T2DM treated by gastric bypass, compared to individuals with T2DM of similar age and body composition not treated by gastric bypass, have been reported to have lower BMD, lower bone strength, and increased levels of several bone turnover markers [45]. Another recent study has also reported that levels of bone turnover markers increased significantly after gastric bypass surgery [46]. Systematic vitamin D and calcium supplementation seems advisable although its beneficial effect on BMD in the post-surgical population remains to be seen.…”
Section: Discussionmentioning
confidence: 99%
“…Relationships of calcium and vitamin D with PTH should be explored further, as PTH may impact bone turnover and bone mineral density (BMD) postoperatively [14][15][16][17][18][19][20][21][22][23][24]. More focus on these are needed during follow-up.…”
Section: Introductionmentioning
confidence: 99%